Droplet microarrays for cell culture: effect of surface properties and nanoliter culture volume on global transcriptomic landscape. (June 2021) - Chakraborty, S.; Gourain, V.; Benz, M.; Scheiger, J.M.; Levkin, P.A.; Popova, A.A.
Abstract: The development of novel chemically developed and physically defined surfaces and environments for cell culture and screening is important for various biological applications. The Droplet microarray (DMA) platform based on hydrophilic-superhydrophobic patterning enables high-throughput cellular screening in nanoliter volumes and on various biocompatible surfaces. Here we performed phenotypic and transcriptomic analysis of HeLa-CCL2 cells cultured on DMA, with a goal to analyze cellular response on different surfaces and culture volumes down to 3 nL, compared with conventional cell culture platforms. Our results indicate that cells cultured on four tested substrates: nanostructured nonpolymer, rough and smooth variants of poly(2-hydroxyethyl methacrylate- co -ethylene dimethacrylate) polymer and poly(thioether) dendrimer are compatible with cells grown in Petri dish. Cells cultured on nanostructured nonpolymer coating exhibited the closet transcriptomic resemblance to that of cells grown in Petri dish. Analysis of cells cultured in 100, 9, and 3 nL media droplets on DMA indicated that all but cells grown in 3 nL volumes had unperturbed viability with minimal alterations in the transcriptome compared with 96-well plate. Our findings demonstrate the applicability of DMA for cell-based assays and highlight the possibility of establishing regular cell culture on various biomaterial-coated substrates and in nanoliter volumes, along with routinely used cell culture platforms. Graphical abstract: Image 1